Long coverage with drug-eluting stents is superior to spot coverage for long femoropopliteal artery disease: PARADE II study - Park, Jong-Il; Ko, Young-Guk; Lee, Yong-Joon; Lee, Seung-Jun; Hong, Sung-Jin; Ahn, Chul-Min; Kim, Jung-Sun; Kim, Byeong-Keuk; Hong, Myeong-Ki; Yu, Cheol-Woong; Rha, Seung-Woon; Park, Jong-Kwan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background The efficacy of spot stenting using drug-eluting stents (DES) for the treatment of long femoropopliteal (FP) lesion is unknown. This study aimed to compare clinical outcomes of long full coverage vs. spot coverage with DES for long FP artery disease. Methods This multicenter randomized trial compared long DES vs. spot DES for FP lesions longer than 150 mm. All lesions were treated with paclitaxel-eluting stents (Zilver PTX). The primary endpoint was primary patency at 12 months. Results The study was terminated early after an interim analysis. A total of 103 patients (55 in the long DES group; 48 in the spot DES group) were eligible for analysis. There were no significant differences in baseline and lesion characteristics between groups. Total stent length was longer in the long DES group than in the spot DES group (225.6 ± 67.2 vs. 131.3 ± 48.7 mm, p < 0.001). Technical success was achieved in all patients. There was a trend toward a higher primary patency rate at 12 months in the long DES group than in the spot DES group (87.5% vs. 67.5%, p = 0.120). The rate of survival free from target lesion revascularization was significantly higher in the long DES group than in the spot DES group (91.7% vs. 72.0%, p = 0.044). In multivariate Cox regression analysis, spot DES [hazard ratio (HR) 2.42, 95% confidence interval (CI) 1.14–5.12, p = 0.021] and postdilation (HR 0.27, 95% CI 0.09–0.79, p = 0.018) were identified as independent predictors for loss of patency at 12 months post-procedure. Conclusions Long DES were more effective than spot DES for treating long FP lesions. Clinical trial registration Clinicaltrials.gov, identifier: NCT02701881.